2008
DOI: 10.1021/ic801275w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of 2D→2D Interpenetrating Coordination Polymers Showing Polyrotaxane- and Polycatenane-like Motifs: Influence of Various Ligands on Topological Structural Diversity

Abstract: A series of mixed-ligand coordination complexes, namely, [Cd 2(bimb) 2(L (1)) 2] ( 1), [Cd(bpimb) 0.5(L (2))(H 2O)] ( 2), [Zn 5(bpib) 2(L (3)) 4(OH) 2(H 2O) 2] ( 3), [Zn(bpib) 0.5(L (4))] ( 4), and [Cd(bib)(L (4))] ( 5), where bimb = 1,4-bis((1 H-imidazol-1-yl)methyl)benzene, bpimb = 1,4-bis((2-(pyridin-2-yl)-1 H-imidazol-1-yl)methyl)benzene, bpib = 1,4-bis(2-(pyridin-2-yl)-1 H-imidazol-1-yl)butane, bib = 1,4-bis(1 H-imidazol-1-yl)butane, H 2L (1) = 4-((4-(dihydroxymethyl)phenoxy)methyl)benzoic acid, H 2L (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…4, compound 1 shows a maximum emission at 453 nm (λ ex = 340 nm). As reported in literatures [44,45], the photoluminescent spectra of free neutral ligands show the emission maxima at 389 nm (λ ex = 246 nm) for HL 2 , 360 nm (λ ex =480 nm) for 1,4-H 2 bdc, respectively. The emission of the HL 2 , 1,4-H 2 bdc ligands may be assigned to π* → n and π* → π transitions of the intraligands.…”
supporting
confidence: 76%
“…4, compound 1 shows a maximum emission at 453 nm (λ ex = 340 nm). As reported in literatures [44,45], the photoluminescent spectra of free neutral ligands show the emission maxima at 389 nm (λ ex = 246 nm) for HL 2 , 360 nm (λ ex =480 nm) for 1,4-H 2 bdc, respectively. The emission of the HL 2 , 1,4-H 2 bdc ligands may be assigned to π* → n and π* → π transitions of the intraligands.…”
supporting
confidence: 76%
“…Complex 1 displays a peculiar trinuclear center-symmetrical unit with CdÁ Á ÁCd inter-distance 3.4872 Å, which built from connecting Cd II ions via the l 2 -oxygen (O5) and l 1 -oxygen (O2, O8). To the best of our knowledge, binuclear structures of Cd are relatively common [15][16][17][18], however trinuclear symmetrical structures are rare of reports. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Among diverse entangled MOFs, interpenetration is the most familiar phenomenon. To date, considerable efforts have been invested in interpenetrating MOFs and a great many interpenetrating networks have been reported by many groups [6][7][8][9] and some comprehensive reviews have been made by Robson, Batten, and Ciani et al [10][11][12] Summarizing from the large amount of reported works, we can draw a conclusion that long and low steric hindrance ligands will lead to larger voids that may result in high-fold interpenetrating structures. [13] Therefore, the effective strategy for constructing interpenetrating MOFs is to use long and low steric hindrance ligands.…”
Section: Introductionmentioning
confidence: 94%